SOME SKETCHES ON MEMORABLE ANNIVERSARIES: GREAT WILLIAM SHAKESPEARE IS 450! 75 YEARS TO “HAMLET” IN PASTERNAK’S TRANSLATION - Tretyakova, T.P. (Perm Federal Research Centre Journal, 2015)
World greatest playwright William Shakespeare has become a part of Russian cultural life and Shakespeare’s 450 birthday celebrations in 2014 witnessed a great number of events, such as conferences, new theater productions, analytical publications and translations - all information now available at the database “Russian Shakespeare” (http://rus-shake.ru).Special emphasis in the article is laid on the Pasternak’s poetic translation of “Hamlet”, and poet’s comments on translation and modern critique.